Blockade of Rostral Ventrolateral Medulla (RVLM) Bombesin Receptor Type 1 Decreases Blood Pressure and Sympathetic Activity in Anesthetized Spontaneously Hypertensive Rats - Pinto, Izabella S.; Mourão, Aline A.; da Silva, Elaine F.; Camargo, Amanda S.; Marques, Stefanne M.; Gomes, Karina P.; Fajemiroye, James O.; da Silva Reis, Angela A.; Rebelo, Ana C. S.; Ferreira-Neto, Marcos L.; Rosa, Daniel A.; Freiria-Oliveira, André H.; et al. (Frontiers in Physiology, 2016)
IIntrathecal injection of bombesin (BBS) promoted hypertensive and sympathoexcitatory effects in normotensive (NT) rats. However, the involvement of rostral ventrolateral medulla (RVLM) in these responses is still unclear. In the present study, we investigated: (1) the effects of BBS injected bilaterally into RVLM on cardiorespiratory and sympathetic activity in NT and spontaneously hypertensive rats (SHR); (2) the contribution of RVLM bombesin type 1 receptors (BB1) to the maintenance of hypertension in SHR. Urethane-anesthetized rats (1.2 g · kg−1, i.v.) were instrumented to record mean arterial pressure (MAP), diaphragm (DIA) motor and renal sympathetic nerve activity (RSNA). In NT rats and SHR, BBS (0.3 mM) nanoinjected into RVLM increased MAP (33.9 ± 6.6 mmHg and 37.1 ± 4.5 mmHg, respectively; p < 0.05) and RSNA (97.8 ± 12.9 % and 84.5 ± 18.1 %, respectively; p < 0.05). In SHR, BBS also increased DIA burst amplitude (115.3 ± 22.7 %; p < 0.05). BB1 receptors antagonist (BIM-23127; 3 mM) reduced MAP (-19.9 ± 4.4 mmHg; p < 0.05) and RSNA (-17.7 ± 3.8 %; p < 0.05) in SHR, but not in NT rats (-2.5 ± 2.8 mmHg; -2.7 ± 5.6 %, respectively). These results show that BBS can evoke sympathoexcitatory and pressor responses by activating RVLM BB1 receptors. This pathway might be involved in the maintenance of high levels of arterial blood pressure in SHR.